2021
DOI: 10.1155/2021/2335805
|View full text |Cite
|
Sign up to set email alerts
|

Performance Investigation of Tempered Glass-Based Monocrystalline and Polycrystalline Solar Photovoltaic Panels

Abstract: Solar photovoltaic (PV) converts sunlight into electricity and is an appropriate alternative to overcome the depletion of conventional fuels and global warming issues. The performance of a PV panel may vary with respect to PV cell technology, fabrication methods, and operating conditions. This research aims at performing an experimental study to investigate the electrical performance of novel tempered glass-based PV panels using two different types of solar cells: monocrystalline and polycrystalline. Tempered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 19 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…Mardy Huot et al, [8] had conducted an experiment to study the electrical performance or efficiency of different PV panels which are monocrystalline and polycrystalline. In short, the PV panels provide more electrical output power when the sun irradiation is higher.…”
Section: Introductionmentioning
confidence: 99%
“…Mardy Huot et al, [8] had conducted an experiment to study the electrical performance or efficiency of different PV panels which are monocrystalline and polycrystalline. In short, the PV panels provide more electrical output power when the sun irradiation is higher.…”
Section: Introductionmentioning
confidence: 99%
“…A water-based PVT system frequently used the thermal absorber's heat transfer fluid, which was abundant behind the second layer, to collect heat [8]. Previous studies have been conducted in order to improve the overall performance of fluidbased PVT by constructing the thermal absorber system with different materials and designs, and achieve electrical and thermal efficiencies around 7.4 -15.5% and 42 -83%, respectively [9][10][11][12]. The literature analysis revealed that silicon-based solar cells are the most widely employed in a wide variety of applications with acceptable electrical efficiency ranges.…”
Section: Introductionmentioning
confidence: 99%